Acessibilidade no processo de inclusão na graduação em Ciências Contábeis: um estudo na Universidade Federal de Uberlândia - Souza, Matheus Silva (2022)
Access to education for people with disabilities in Brazil began with the creation of specialized institutes in the mid-19th century. In basic education, this access was only ensured in the mid-twentieth century, at first in separate classrooms from other students. As students with disabilities completed their education in regular education, the demand for access to higher education by this public increased. However, various barriers - lack of accessibility, lack of institutional resources, and need for teacher training - limit the guarantee of access, permanence, and completion of higher education for people with disabilities, and therefore the elimination of these barriers is essential for successful academic of students with disabilities, as well as for the guarantee of fundamental rights such as education, maintaining, thus social justice (RAWLS, 1997). When analyzing inclusion through the lens of accessibility dimensions (SASSAKI, 2009), we seek to identify how accessibility, in its different dimensions, is promoted [and perceived] in Accounting Sciences courses and at the Federal University of Uberlândia. The discussion was held through the use of a qualitative approach, and through the technique of content analysis, we sought to interpret and assign meanings to the terms and expressions used by a corpus investigated by 29 (twenty-nine) participants of this research, about accessibility in the process of inclusion in undergraduate courses in Accounting offered by the Federal University of Uberlândia. The categories, objects of analysis, comprised educational inclusion; the dimensions of accessibility [architectural, instrumental, communicational, methodological, attitudinal, and programmatic]; challenges, achievements and difficulties of inclusion. The results suggest that public policies played a very important role in providing access to people with disability to higher education. However, students with disabilities enrolled in the Accounting Sciences at the Federal University of Uberlândia reported difficulties during its formative path, regarding the different dimensions of accessibility, highlighting among them irregular signage on the tactile floor, unpaved parking, defective elevators, difficulties in accessing the auditorium, need for equipment of instrumental accessibility, difficulties in meeting the demand for a Libras interpreter, unavailability of guide-interpreter for students with visual impairments, and absence of material and bibliographic collection in sign language or Braille, the need to train to teach, use of terms technicians that make it difficult for deaf students to understand and disability discrimination attitudes in the space university, failure of communication between the direction, coordination, Depae, and student, regarding registration and declaration of disability. Therefore, the effectiveness of inclusive education for students with disabilities in higher education involves several factors - implementation of public policies, application of resources, and promotion of accessibility in its dimensions.